An evaluation reading of the paperless implementation system in the judicial system in KSA – An applied study on the execution courts in Asir region – - al-Shahrani, Abd al-Salam bin Marie; Al-Shahrani, Saeed bin Ayed (Journal of Economic, Administrative and Legal Sciences, 2020)
The aim of this research is to find obstacles to the implementation of the Paperless Implementation System from the perspective of the users of the system in the Execution Courts. This system was recently launched as an alternative to the manual system. To find and limit those barriers، users were classified into categories such as judges، employees، users and beneficiaries. The data was collected from those targeted through a questionnaire distributed to them. These data were analyzed using SPSS. The results showed that there are a number of obstacles that are related to administrative obstacles، technical obstacles and human obstacles at close rates. The researcher recommended some training for the users of the system as well as creating an appropriate administrative environment for the users.